DOI: 10.11606/t.18.2017.tde-02022017-152135
|View full text |Cite
|
Sign up to set email alerts
|

Análise experimental do efeito da geometria da seção transversal e do desempenho de fluidos de reduzido GWP na ebulição convectiva em canais de dimensões reduzidas

Abstract: Agradeço inicialmente ao Prof. Gherhardt, pela oportunidade concedida para realizar o doutorado, pela excelente orientação, formação acadêmica e amizade brindada no decorrer do doutorado.À Fundação de Apoio à Pesquisa do Estado de São Paulo, FAPESP, pela bolsa de estudos concedida para a realização deste doutorado (N°Processo 2010/17605-4).A Jose Roberto Bogni, pela amizade e ajuda na montagem da bancada experimental.Um agradecimento especial ao professor William Gonzáles Mamani pela formação acadêmica durante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Chauhan and Kandlikar [6] pointed out that commercial air-cooling technology can dissipate up to 9 W/cm 2 , while the microprocessor can dissipate as much as 750 W/cm 2 or even higher heat fluxes [7]. In this context, Agostini et al [8] reported a study conducted by an international consulting company that identified a need of a technological transition from traditional air-cooling methods to more sophisticated and efficient cooling solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan and Kandlikar [6] pointed out that commercial air-cooling technology can dissipate up to 9 W/cm 2 , while the microprocessor can dissipate as much as 750 W/cm 2 or even higher heat fluxes [7]. In this context, Agostini et al [8] reported a study conducted by an international consulting company that identified a need of a technological transition from traditional air-cooling methods to more sophisticated and efficient cooling solutions.…”
Section: Introductionmentioning
confidence: 99%